Quality analysis of various surface water bodies in the GAM and the osa peninsula using the Dutch Index - Calvo-Brenes, Guillermo (2012)
Costa Rica is characterized by the amount of rivers, but most of them show high levels of contamination. Special interest is in those of the Gran Area Metropolitana (GAM) since 70% of the population is located in this area. Even though there are many water quality indicators, it is advantageous the simplification by the use of water quality index. One of those already adopted in Costa Rica is the Holland Quality Index (Holland ICA).This is based on the use of three parameters: biochemical oxygen demand, ammonium nitrogen and the dissolve oxygen, expressed the last one as saturated oxygen percentage. This study focused in the analysis of the three parameters in 10 rivers located in the province of San José, Alajuela, Heredia, Car tago, as well as the Península of Osa. For the correlation of the Holland ICA with Population Density, there were sampled 3 places of the same river: one high up place close to the river birth, another in the middle, and the last one, close to the exit. It was found the rivers going through high density cities with populations over 8000 habitants per square kilometer (hab/km2), shows contamination corresponding to “severe” and “highly severe”. Places with population between 3000-8000 hab/km2, in general, shows contamination between “moderate” to “severe”. Places with less than 1000 hab/km2 are related to contamination levels of “lightly” to “none”. Those results vary depending of rivers flow rate, the total distance alongside the river, as well as the land use. The Univariate Regression Analysis showed positive correlation between Holland ICA and population density, with a 95% probability.